PEMAHAMAN KONSEP IPAS SISWA KELAS IV DI SDN 07 SUNGAI RAYA : Penelitian Skripsi - Rizkiawati Hanami; Dessy Setyowati; Risdiana Andika Fatmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the conceptual understanding of IPAS (Science and Social Studies Integration) among fourth-grade students at SDN 07 Sungai Raya on the topics of muscular force and friction force, using Anderson's indicators of understanding. The research employed a descriptive quantitative approach. The sample consisted of all 23 students in class IVE. Data were collected through a written test comprising 6 essay questions based on six of Anderson’s understanding indicators: interpreting, exemplifying, classifying, concluding, comparing, and explaining. The results show that students' average conceptual understanding is categorized as moderate level, with an average score of 69. The highest achievements were in the indicators of exemplifying (89%) and explaining (80%). The indicators of concluding (70%) and classifying (71%) were also categorized as high. The comparing indicator was categorized as moderate (63%), while interpreting was categorized as low (40%).